2022
DOI: 10.3389/fpls.2022.868350
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Supplementation as a Biostimulant in Medical Cannabis (Cannabis sativa L.) Plant Nutrition

Abstract: There is growing evidence to support the involvement of nutrients and biostimulants in plant secondary metabolism. Therefore, this study evaluated the potential of amino acid-based supplements that can influence different hydroponic nutrient cycles (systems) to enhance the cannabinoid and terpene profiles of medical cannabis plants. The results demonstrate that amino acid biostimulation significantly affected ion levels in different plant tissues (the “ionome”), increasing nitrogen and sulfur content but reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Undoubtedly, nutrition plays a pivotal role in shaping the development, functionality, and metabolic processes of various plant organs and tissues ( Shiponi and Bernstein, 2021b ; De Prato et al., 2022 ). Existing knowledge has extensively documented the ideal thresholds of specific macronutrients, including N, P and K, along with micronutrients like Fe, necessary for ensuring the normal growth and functioning of both root systems and above-ground biomass ( Shiponi and Bernstein, 2021a ; Shiponi and Bernstein, 2021b ; Malík et al., 2022 ; Saloner and Bernstein, 2022 ; Llewellyn et al., 2023 ), as well as the production of valuable secondary metabolites in medicinal cannabis plants ( Caplan et al., 2017 ; Bernstein et al., 2019b ; Shiponi and Bernstein, 2021b ; Saloner and Bernstein, 2022 ). It is crucial to emphasize that nutrient solution fertigation was provided to the plants only up to the ninth week of cultivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undoubtedly, nutrition plays a pivotal role in shaping the development, functionality, and metabolic processes of various plant organs and tissues ( Shiponi and Bernstein, 2021b ; De Prato et al., 2022 ). Existing knowledge has extensively documented the ideal thresholds of specific macronutrients, including N, P and K, along with micronutrients like Fe, necessary for ensuring the normal growth and functioning of both root systems and above-ground biomass ( Shiponi and Bernstein, 2021a ; Shiponi and Bernstein, 2021b ; Malík et al., 2022 ; Saloner and Bernstein, 2022 ; Llewellyn et al., 2023 ), as well as the production of valuable secondary metabolites in medicinal cannabis plants ( Caplan et al., 2017 ; Bernstein et al., 2019b ; Shiponi and Bernstein, 2021b ; Saloner and Bernstein, 2022 ). It is crucial to emphasize that nutrient solution fertigation was provided to the plants only up to the ninth week of cultivation.…”
Section: Discussionmentioning
confidence: 99%
“…These methods, combined with intensive breeding, have increased yields of female inflorescences and their THC (Δ 9 -tetrahydrocannabinol) levels ( Toonen et al., 2006 ) and improved cannabinoid profile uniformity by altering plant architecture ( Danziger and Bernstein, 2021 ). Indoor cultivation now incorporates automated systems ( Malík et al., 2022 ), with hydroponics gaining popularity for its potential to yield high-quality plant material ( Bouchard and Dion, 2009 ; Vanhove et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…They observed that applying urea with both the inhibitors significantly affected the qualitative and agronomic characteristics, such as increased CBD content, in the two varieties evaluated. Amino acid biostimulant supplements may help standardize the content of secondary metabolites in hemp plants for biomedical purposes, increasing phytocannabinoid production, as observed by Malik et al (2022) [147].…”
Section: Nutrition and Substratementioning
confidence: 96%
“…A recent study by De Prato et al (2022) examined the growth and cannabinoid production of tropical/subtropical hemp varieties under tropical daylengths, temperatures, and different nitrogen rates. The concentrations of cannabinoids, specifically THC, CBD, and CBN, were found to increase with longer daylengths, leading to an extended vegetative phase characterized by heightened photosynthetic activity that with the N supply contributed to increased production of primary and secondary metabolites (De Prato et al, 2022).…”
mentioning
confidence: 99%
“…The ameliorating effect of biostimulants on salt stress has also been investigated in other horticultural crops. El-Nakhel et al (2022) reported that the application of LDPH mitigated the detrimental impacts of high salinity (EC levels up to 6 dS m -1 ) in spinach plants. Lucini and colleagues (2015) observed improvements in lettuce growth when treated with a plant-derived biostimulant under saline conditions.…”
mentioning
confidence: 99%